Desain Pit Penambangan Pada Tambang Nikel Desa Wailukum Kabupaten Halmahera Timur - Arfansyah, Muh.; Anshariah, Anshariah; Nawir, Alfian (Jurnal of Mining Insight, 2023)
One of the important aspects of mining planning is the activity of planning and designing mines based on feasibility studies and the final results of exploration of excavated materials. The purpose of this study is to design a mining pit design based on the level distribution pattern and ultimate pit limit. The data used in writing this thesis are assay data,  collar data, geological data, survey data, topographic maps, and coordinates of the research area. Data processing was carried out using Ms. Excell's software to import the database and change the data format to comma separated value, followed by the creation of a model of the pattern of laterite nickel deposits, determination of mining limits on laterite nickel deposit blocks, determination of mining methods, and design  of pit designs mining using Surpac 6.3 software. Based on the research that has been conducted, it can be concluded that based on the pattern of nickel content distribution and the recommendations of the results of the geotechnical study, the  design of the mining pit has the results of bench  geometry and overall slope, namely a bench height  of 5 meters with a width of 3.5 meters and an overall slope of 45º, in accordance with the recommendations of the geotechnical section.